La Politique audiovisuelle en Irlande et au Canada face à l’impérialisme culturel américain - Alexandra Slaby (Revue LISA)
Ireland and Canada face the common challenge of having to protect their cultural production which is a cornerstone of their national identity from American attempts at breaking down any barrier preventing the free circulation of goods and services, including culture. Canada—and especially Québec—has developed a tradition of loud and vocal opposition to what is perceived as American cultural imperialism. On the other hand, Ireland is less critical of the occupation of its audiovisual space by American productions on the strength of its historical ties with the United States. In Ireland, broadcasting comes under the control auspices of a government department which is not otherwise related to cultural issues. The ruling party Fianna Fáil has adopted a purely liberal approach to its national broadcaster, whereas, on the other side of the Atlantic, Canadian official discourse on the matter has grown closer to the European notion of a cultural exception or exemption in favour of culture in order to preserve the core of national identities in the face of globalization.